Financial performance and Corporate social responsibility in the UK listed firms - Ren, Jiaping (2019)
The dissertation investigates the linkage between the social performance and financial performance of the UK listed companies. There was recently a move towards greater concern about the social and environmental issues among the corporations. Such behaviour from the theoretical point of view can be explained using quite a number of different theories. For example, the stakeholder theory, as well as positive accounting theory, the legitimacy theory, to name a few. Predictions from these theories are occasionally quite different from one another. Therefore, there is a need to empirically test the actual link between social and financial performance. For the purpose of such analysis, a sample of 30 firms from amongst the FTSE100 constituent firms was obtained, and data about the social and financial performance of these companies were acquired for the 2014 – 2018 years. Regression analysis was performed in order to evaluate potential linkages form social performance to financial performance. Three aspects of broader social performance were considered – social as such, environmental and governance. The relevance of governance performance relates to the agency costs theory and the ability of effective governance to alleviate the agency problem. The results showed that there is a general negative relationship between social and financial performance of the considered UK firms. The result, in fact, does only refer to the linkage from the environmental performance to the financial performance. The regulations about environmental reporting and performance are among the strictest as compared to other aspects of broader social performance. The impact of the social performance and the governance performance on ROE and ROA was not statistically significant. The findings are suggestive of the relevance of the legitimacy theory and that of the stakeholder view of the corporation, as the relevant theoretical frameworks that explain the behaviour of the considered UK corporations.